Challenging the Legal Structures of Dispossession from the Local - Gómez Rojas, Ana Carolina (2024)
Latin America is framed within a neoliberal rationality that favors the installation of legal structures of dispossession (LSD) (Hernández, 2019). However, local communities resist and counterattack in diverse ways, including legal and political. A space for observing these dynamics is the socio-environmental conflict derived from the La Colosa gold mining project in Colombia, since, through the use of mechanisms such as popular consultation, new institutional agreements have been reached challenging the traditional distribution of power over the territory. The central argument is that the case of resistance to megaprojects through legal mechanisms helps to observe the processes of institutionalized resistance that transform legal structures to give way to a different relationship between nature-society. Methodologically, the argument is based on participant and participatory observation, semi-structured interviews, documentary, and journalistic review between 2013 and 2022, and review of judicial documents from a documentary ethnography perspective (Muzzopappa & Villalta, 2013). Despite the asymmetry of power in which socio-environmental disputes develop, the results show that there are multiple interactions challenging the hegemonic power from the local level, forcing it to a permanent territorial reflexivity. In addition, it is based off the responses from organized communities, public authorities, and corporations that the strategies for the following stages of the conflict arise. This implies that any conflict is not beforehand resolved.